Multicoated elliptic fibrous composites of piezoelectric and piezomagnetic phases - Kuo, Hsin-Yi (My University, 2011)
A theoretical framework is developed to investigate the magnetoelectroelastic potential in a multicoated elliptic fibrous composite with piezoelectric and piezomagnetic phases. We generalize the classic work of Rayleigh (1892) to obtain the electrostatic potential in ordered conductive composites and its extension to a disordered system (Kuo, 2010; Kuo & Chen, 2008) to the current coupled magnetoelectroelastic multicoated elliptic composites. We combine the methods of complex potentials with a re-expansion formulae and the generalized Rayleigh's formulation to obtain a complete solution of the multi-field many-inclusion problem. It is shown that the coefficients of field expansions can be written in the form of an infinite set of linear algebraic equations. Numerical results are presented for several configurations. We use this method to study BaTiO(3)-CoFe(2)O(4) composites and find that, with appropriate coating, the effective magnetoelectric voltage coefficient can be enhanced with one order of magnitude compared to their non-coating counterpart. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Magnetoelectricity; Piezoelectric; Piezomagnetic; Elliptic fibrous composite; Multicoated